Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1089/jwh.2013.4572
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic Load in Women with a History of Low Birth Weight Infants: The National Health and Nutrition Examination Survey

Abstract: Background: The purpose of our study was to determine whether women of reproductive age with history of low birth weight (LBW) deliveries have higher allostatic load (AL), a measure of the cumulative toll of chronic stress, than those with normal-weight deliveries. Methods: We used data from women ages 17-35 who responded to the National Health and Nutrition Examination Survey (NHANES) reproductive-health questionnaire, 1999-2006. Women reported history of LBW infants and those who were preterm. We classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 34 publications
(34 reference statements)
4
48
0
Order By: Relevance
“…In this regard, experiencing racial discrimination, and the exclusion that ensues, elicits a stress response that has detrimental effects on health . Briefly, allostatic load represents the chronic physiologic and psychosocial stress experienced over the life course by combining several markers of physical function into a composite score of biologic risk . Research has demonstrated that women with a history of small‐for‐gestational‐age birth or preterm birth have higher allostatic load than those women giving birth to normal birth weight infants .…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…In this regard, experiencing racial discrimination, and the exclusion that ensues, elicits a stress response that has detrimental effects on health . Briefly, allostatic load represents the chronic physiologic and psychosocial stress experienced over the life course by combining several markers of physical function into a composite score of biologic risk . Research has demonstrated that women with a history of small‐for‐gestational‐age birth or preterm birth have higher allostatic load than those women giving birth to normal birth weight infants .…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…This quantification of AL has proved its explanatory power in understanding the relationship between specific stressors and physical health, initially using data from the MacArthur Studies of Successful Aging (39) and National Health and Nutrition Examination Survey (NHANES) data for adults (14). More recently, AL has been employed to predict risk of adverse reproductive (40) and pediatric health outcomes (5), although empiric evidence on its utility in pregnancy is conflicting (35,41). Incorporation of a profile of biomarkers for stress, aging, and immune response may permit a more comprehensive and predictive AL assessment.…”
Section: Allostasis and Allostatic Loadmentioning
confidence: 99%
“…Thus, AL is the biological result of chronic overactivity of these stress response pathways (Hux & Roberts, ), which over time leads to systemic dysregulation across numerous biological systems and increased risk for chronic disease. Indeed, a vast body of literature has linked elevated AL to a myriad of chronic diseases in adulthood, including a variety of psychological disorders (Beckie, Duffy, & Groer, ; Kuhn et al, ), cardiovascular disease (Havranek et al, ; Steptoe & Kivimaki, ), diabetes (Steptoe et al, ), and adverse pregnancy outcomes (Hux, Catov, & Roberts, ; Hux & Roberts, ), as well as others. However, there is a lack of consistency across the literature in how AL is operationalized and scored, which makes the comparison and validity of findings across studies challenging (Beckie, ).…”
Section: Introductionmentioning
confidence: 99%